Moisture transport in cotton woven fabrics of different weaves and linear density of weft yarn - Dominika Kamińska; Małgorzata Matusiak (Communications in Development and Assembling of Textile Products)
Cotton is the most common raw material of natural origin applied in clothing manufacturing. Clothing currently available on the market is usually made of plain weave fabrics. As part of this study, 3 pairs of cotton woven fabrics with different weaves (plain, twill 2/2 S, transverse rep 1/1) and different linear density of weft yarn (60 tex and 100 tex) were tested. The scope of research included determination of parameters characterizing the ability of fabrics to transport moisture in liquid form. The investigation was carried out on the Moisture Management Tester M290. The investigations allowed assessing the moisture transport of individual fabrics as well as the influence of both weave and linear density of weft yarn on the parameters characterizing the liquid moisture transport in the fabrics.